2016
DOI: 10.1523/jneurosci.0007-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Helix 12 in Munc18-1 Induces Vesicle Priming

Abstract: Munc18-1 is essential for vesicle fusion and participates in the docking of large dense-core vesicles to the plasma membrane. Recent structural data suggest that conformational changes in the 12th helix of the Munc18-1 domain 3a within the Munc18-1:syntaxin complex result in an additional interaction with synaptobrevin-2/VAMP2 (vesicle-associated membrane protein 2), leading to SNARE complex formation. To test this hypothesis in living cells, we examined secretion from Munc18-1-null mouse adrenal chromaffin ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 61 publications
(72 reference statements)
5
70
2
Order By: Relevance
“…Note that Munc18 expression has been described to cause increased syntaxin-1 targeting to the plasma membrane (Gulyas-Kovacs et al. , 2007); however, in the present context, we always quantified the total syntaxin-1 immunolabeling of the cell, which is not significantly changed during short-term Munc18-1 overexpression (Munch et al. , 2016).…”
Section: Resultsmentioning
confidence: 97%
“…Note that Munc18 expression has been described to cause increased syntaxin-1 targeting to the plasma membrane (Gulyas-Kovacs et al. , 2007); however, in the present context, we always quantified the total syntaxin-1 immunolabeling of the cell, which is not significantly changed during short-term Munc18-1 overexpression (Munch et al. , 2016).…”
Section: Resultsmentioning
confidence: 97%
“…Mammalian MUNC18 and homologous C. elegans UNC-18 interact with SNARE protein complexes to regulate docking, priming, and exocytosis of SVs and DCVs (50,51,57,58,(61)(62)(63). Repetitive electrical stimulation of murine auditory and cerebellar synapses substantially raises the rate of NT release (15,54).…”
Section: Discussionmentioning
confidence: 99%
“…A homology-based model places serines 311 and 322 in a loop that links two antiparallel ␣-helices in the UNC-18 3a domain (55). Structures determined for homologous MUNC18 and its binding partners revealed that segments of the ␣-helix adjoining the C terminus of the specified loop mediate interactions with v-and t-SNARE complexes and syntaxin (61)(62)(63). This suggests that Ser 311 and Ser 322 are well positioned to participate in the reversible regulation of UNC-18 functions via phosphorylation and dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Munc18-1 stabilizes the t-SNARE complex, which is required for efficient docking (15). Furthermore, Munc18-1 induces Tc folding and the NTD conformational change, activating the t-SNARE complex to initiate SNARE zippering (8,32,33). Note that Munc18-1 also binds to SNAREs in other modes that play crucial roles in SNARE assembly (8,14,31).…”
Section: Discussionmentioning
confidence: 99%
“…The NTD of the native SNARE complex slowly assembles but readily disassembles upon vesicle undocking (8,9), limiting the overall rate of SNARE assembly and membrane fusion. Munc18-1 and other regulatory proteins enhance NTD assembly to initiate SNARE zippering (17,31,32). Vc-57 significantly increased the rate and stability of NTD assembly, suggesting that this peptide efficiently activated the t-SNARE complex to initiate SNARE zippering.…”
Section: Effect Of T-snare Conformational Switch On Ternary Snare Zipmentioning
confidence: 99%